Edukasi Pedoman Gizi Seimbang Pada Anak Sekolah dalam upaya pencegahan obesitas di SDN 005 Lubuk Baja , Kota Batam - Siska Pratiwi; Haqqelni Nur Rosyidah; Aprilya Roza Werdani; Desy Desy; Roza Erda (BADAN PENERBIT STIEPARI PRESS, 2022)
A balanced menu is consuming food to meet the body's need for nutrients. Nutritional deficiencies in one food by providing a balanced menu can be fulfilled by other foods. For this reason, providing a balanced menu with a variety of foods is very necessary to meet nutritional adequacy. The aim of this activity is to socialize guidelines for balanced nutrition and what's on my plate to school children as an effort to prevent obesity. The implementation method in this service is question and answer and discussion using poster media. The target group for this service is students in Classes 4, 5, and 6 of SDN 005 Lubuk Baja. The results of the community service show that the students' knowledge has increased as seen from the results of the pre-test and the post test is 60 points, with the lowest score being 6 and the highest being 47. It is hoped that after this service the students of SDN 005 will be able to eat foods in accordance with the guidelines for balanced nutrition for school children.